Physical activity and health state selfperception by portuguese adults - Mendes, Francisco (2017)
According to the World Health Organization (2015) [1], physical activity translates into significant health benefits and the lack of its practice constitutes a fundamental risk factor in non-transmitted diseases. Objectives: to determine physical activity levels in adults that go (N = 150) or do not go (N = 206) to a gym and relate them with health self-perception (from mediocre to very good).